Effects of Dietary Protein-to-Energy Ratios on Growth, Immune Response, Antioxidative Capacity, Liver and Intestinal Histology, and Growth-Related Gene Expression in Hybrid Yellow Catfish (Pelteobagrus fulvidraco ♀ × Pelteobagrus vachelli ♂) - Sehrish Taj; Quan Han; Xiaoyi Wu; Haoran Yin; Lixia Tian; Huijun Yang; Yongjian Liu; Junwa Huang (Aquaculture Nutrition)
This study is aimed at evaluating the effects of dietary protein-to-energy ratios on the growth, immunological response, antioxidative capacity, liver and intestinal histology, and growth-related gene expression of hybrid yellow catfish (Pelteobagrus fulvidraco ♀ × Pelteobagrus vachelli ♂). Eight diets were formulated to form different protein/energy ratios of 84, 88, 90, 93, 95, 96, 99, and 103 mg/kcal (P/E84, P/E88, P/E90, P/E93, P/E95, P/E96, P/E99, and P/E103), respectively. These diets contain different levels of gross energy (GE), ranging from 4.13 to 4.76 kcal g-1. Seven hundred and twenty healthy fish (17.15±0.02 g) were randomly dispersed into 24 rectangular fiberglass tanks with 8 treatments in triplicate groups. The fish fed a P/E ratio of 95 mg/kcal demonstrated the best growth and feed utilization. A significant (P<0.05) increase in percent weight gain (WG%) and specific growth rate (SGR) was seen as the dietary P/E ratio ameliorated from P/E84 to P/E95, followed by a decreased pattern in these parameters. Feed conversion ratio (FCR) and daily feed intake (DFI) were significantly impacted by dietary P/E ratios (P<0.05). Additionally, an optimum P/E ratio improved intestinal morphology. However, low or high P/E ratio diets can cause oxidative stress, impaired liver function, and significantly reduced nonspecific immunity. The expression of target of rapamycin (TOR) and insulin-like growth factor-1 (IGF1) genes in the liver was considerably influenced by dietary protein-to-energy ratios (P<0.05). Based on the statistical analysis of WG% against the dietary P/E ratio, the optimal P/E ratio for the studied species was estimated to be 92.92 mg/kcal.